A Review of Role and Challenges of Non-Banking Financial Companies in Economic Development of India - Nazneen, Afroze; Dhawan, Sanjeev (International Journal of Economics and Financial Issues, 2018)
For a large and diverse country like India, ensuring financial access to penetrate growth and entrepreneurship is a critical priority. In this scenario, the Non-Banking Finance Companies (NBFCs) sector has scripted a story that is remarkable. It speaks to the truly diverse and entrepreneurial spirit of India. From large infrastructure financing to small microfinance, the sector has innovated over time and found ways to address the debt requirements of every segment of the economy. To its credit, the industry has also responded positively to regulatory efforts to better understand risks and to address such risks through regulations. Over time, the sector has evolved from being fragmented and informally governed to being well regulated and in many instances, adopted best practices in technology, innovation and risk management as well as governance. In the light of this, the present study encompasses the role and challenges faced by NBFCs in Economic Development of India. Keywords: NBFCs, Banks, Financial Institutions, Lease and Hire, Purchase and Assets Growth JEL Classification: G2 DOI: https://doi.org/10.32479/ijefi.7220